Observation of the Decay Λ0b→Λ+cτ−ν[bar]τ - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2022)
The first observation of the semileptonic b-baryon decay Λ0b→Λ+cτ−¯ντ, with a significance of 6.1σ, is reported using a data sample corresponding to 3 fb−1 of integrated luminosity, collected by the LHCb experiment at center-of-mass energies of 7 and 8 TeV at the LHC. The τ− lepton is reconstructed in the hadronic decay to three charged pions. The ratio K=B(Λ0b→Λ+cτ−¯ντ)/B(Λ0b→Λ+cπ−π+π−) is measured to be 2.46±0.27±0.40, where the first uncertainty is statistical and the second systematic. The branching fraction B(Λ0b→Λ+cτ−¯ντ)=(1.50±0.16±0.25±0.23)% is obtained, where the third uncertainty is from the external branching fraction of the normalization channel Λ0b→Λ+cπ−π+π−. The ratio of semileptonic branching fractions R(Λ+c)≡B(Λ0b→Λ+cτ−¯ντ)/B(Λ0b→Λ+cμ−¯νμ) is derived to be 0.242±0.026±0.040±0.059, where the external branching fraction uncertainty from the channel Λ0b→Λ+cμ−¯νμ contributes to the last term. This result is in agreement with the standard model prediction.
Im Titel sind die Buchstaben b und c tiefgestellt
Im Titel sind die Zahl 0 und die Zeichen + und - hochgestellt
Im Titel steht "nu" mit einem Oberstrich
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kepcna, B. Leverington, P. Li, H. Malygina, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und 985 weitere Personen]
Gesehen am 21.07.2022